2012
DOI: 10.1017/cbo9781139207805
|View full text |Cite
|
Sign up to set email alerts
|

A Concise History of Modern India

Abstract: A Concise History of Modern India by Barbara D. Metcalf and Thomas R. Metcalf, has become a classic in the field since it was first published in 2001. As a fresh interpretation of Indian history from the Mughals to the present, it has informed students across the world. In the third edition of the book, a final chapter charts the dramatic developments of the last twenty years, from 1990 through the Congress electoral victory of 2009, to the rise of the Indian high-tech industry in a country still troubled by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…The majority (99.2%) of the adult study population experienced or witnessed at least one traumatic event during their lifetime (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], with an average of 7.7 (SD 4.0) traumatic events per person. Men reported that they had witnessed or experienced more traumatic events than women (mean 8.4 (SD 4.2) and 6.4 (SD 3.8), respectively; p<0.001) (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The majority (99.2%) of the adult study population experienced or witnessed at least one traumatic event during their lifetime (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], with an average of 7.7 (SD 4.0) traumatic events per person. Men reported that they had witnessed or experienced more traumatic events than women (mean 8.4 (SD 4.2) and 6.4 (SD 3.8), respectively; p<0.001) (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Even though suspending elected institutions through PR is an emergency power, Article 356 has often been declared "in circumstances where it was perfectly clear that a breakdown in constitutional authority had not taken place". 59 The provision has been misused to "intimidate recalcitrant state governments", 60 and to resolve intra-party conflicts. 61 Episodes of PR are thus akin to "interrupted regimes" in cross-national research.…”
Section: Autonomymentioning
confidence: 99%
“…The results of ambitious land reforms in the 1950s were limited as large landlords evaded new land-ownership ceilings through such simple tactics as distributing title deeds among family members. 47 The failure of land reform following independence led to the persistence of land inequality into the modern era. Panel 2.1 of Figure 2 shows that district-level land inequality, measured by the 1991 land Gini index, is highly correlated with the duration of British rule.…”
Section: Land Inequalitymentioning
confidence: 99%